Spreading The Love with children of Permata Al-Insyirah in Sungai Isap - Siti Nurfarmy, Ibrahim (2019)
A total of 19 Universiti Malaysia Pahang (UMP) students took part in a programme called, ‘Spread the Love’ with orphans and children of Permata Al-Insyirah Orphanage in Sungai Isap, Kuantan that was held on April 13, 2019.